PERAN PEMERINTAH KABUPATEN GUNUNGKIDUL DALAM PENANGANAN PINJAMAN BERMASALAH PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERDESAAN - Meiga Alfa Prananda; Purwoko .; D Ghulam Manar (Journal of Politic and Government Studies, 2016)
PNPM Mandiri Perdesaan is a program to alleviate poverty by providing soft loans without collateral to poor households in order poverty in the area. This program is part of program development of the District Development Program (KDP) and expected to be a solution for poor households by providing venture capital and the development of survival skill independently in accordance to principle of community empowerment. Problems that occurred in the implementation emergence of issues in the group of beneficiary communities that resulted in the group cannot afford to pay installment loans such as in Gunungkidul Regency, where nearly 10% of funds raised by the government in 2014 and then payment jammed, thus the funds are difficult to develop and channeled back to the other poor households. Based on the research, there are several problems that occurred in the group of beneficiary communities, therefore they cannot pay the loan installments. It is from low quality of the human resources in managing grants and their business activities that caused bankruptcy. Awful control by UPK onfacilitators to the use of loan funds beyond the requirement proposed in the proposal and an atrocious verification system breed funds abuse by the group members. Eventhough the local government are not disadvantaged by no return of funds that have been introduced, but in term of reservation of government programs it is suffer losses because of the poverty alleviation program becomes constrained due to no return of loan funds provided to the public. Governments and relevant stakeholders should immediately make improvements in terms of support groups, system verification, and enforcement of sanctions to the troubled group. Keywords: Role of Government, PNPM Mandiri Perdesaan’s Troubled Loan.